The man-made world : or, our androcentric culture - Gilman, Charlotte Perkins 1860-1935. (London : T. Fisher unwin., 1911)
Gilman argues that men's superior position in society is not natural but rather the product of their political, economic, and social advantages.
Electronic reproduction.
Keywords: Women -- Social conditions